THE ASPECTS OF KASAMPURNANING URIP IN LYRICS OF INGSUN SONG BY SUJIWO TEJO - Rusyidah, Halimah Ratna; Setyani, Turita Indah (International Review of Humanities Studies, 2021)
The perfection of life in Javanese society is an achievement when the personal life and God have become one. The concept is usually found in literary works that have a mystical aspect, such as a song called Ingsun by Sujiwo Tejo. For connoisseurs of the song ingsun, the song has a meaning of divinity. This study aims to describe the aspects of perfection in life contained in the lyrics of the song. The study used a qualitative method with interpretive analysis from the perspective of Javanese belief. Based on the discussion kasampurnaning urip or perfection of life in the lyrics of the song Ingsun by Sujiwo Tejo is the ultimate goal of human life. This was achieved by always being aware of two important aspects, namely sangkan paraning dumadi and manunggaling Gusti servants. Manunggaling Kawula Gusti stage is done by restoring the awareness that the place of man to lean on is only to Gusti or God in him in the form of love and affection, namely God as Ar Rahman and Ar Rahkim. With these findings, it can be concluded that humans who have attained kasampurnaning urip always nurture their love for their fellow-creatures and God.